2016
DOI: 10.18831/djmicro.org/2016011001
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of Bacillus Species Bacteria from Sago Industrial Waste

Abstract: Amylase is one of the significant enzymes which are of much use in the real world. These enzymes convert complex starch molecules into glucose or simple sugar units. Amylases are widely used in a number of industrial processes such as food, fermentation, textile, paper, detergent and pharmaceutical industries. Enzymes from fungal and bacterial sources play a key role in industrial sectors. Amylases are classified into three types: α-amylase, β-amylase and γ-amylase. α-Amylase is obtained from plants, animals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This type of tumor microenvironment could be more common or could cause tumors to become more aggressive. However, the vitamin D inflammation pathways have not been a wellexplored mechanism in tumor pathogenesis and progression [20,21].…”
Section: Demographic Featuresmentioning
confidence: 99%
“…This type of tumor microenvironment could be more common or could cause tumors to become more aggressive. However, the vitamin D inflammation pathways have not been a wellexplored mechanism in tumor pathogenesis and progression [20,21].…”
Section: Demographic Featuresmentioning
confidence: 99%
“…Several studies have shown that cell phones contaminated with pathogenic bacteria play a big role in the spread of infectious disease (Brady et al, 2006;Tagoe et al, 2011). Many users do not generally know the microbial load on many regular objects within their living and workplaces (Al-Ghamdi et al, 2011;Shalinimol, 2016). The unclean ways of handling such objects make them a cardinal reservoir of an assembly of pathogenic microorganisms (Zakai et al, 2016;Adhikari et al, 2018) thus mobile cell phones surfaces might serve as fomites in the transmission of these microbes (Bhoonderowa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%